A seven-fold rise in the probability of exceeding the observed hottest summer in India in a 2 °C warmer world. (15th April 2020) - J S, Nanditha; van der Wiel, Karin; Bhatia, Udit; Stone, Dáithí; Selton, Frank; Mishra, Vimal
Abstract: Heatwaves and extreme temperatures during summer (April–May) in India have profound implications on public health, mortality, water availability, and productivity of labourers. However, how the frequency of the hottest summers in observed record (1951–2015) will change under the warming climate in India is not well explored. Using observations from the India Meteorological Department, we show that mean maximum summer temperature has increased significantly in three (arid, monsoon, and savannah) out of five major climatic regions of India during 1951–2015. We identify the hottest summer in the observed record in the five climatic regions in India. The arid, cold, and temperate regions experienced the hottest summer in 2010 while monsoon and Savannah regions witnessed the hottest summer in 1979 and 1973, respectively. Based on simulations from the Climate of 20th Century Plus (C20C+) Detection and Attribution project, we show that the regional hottest summer of 2010 can be attributed to the anthropogenic warming. We then use simulations of a large (2000 year) ensemble of the EC-Earth model to estimate the exceedance probability of the observed hottest summer in the present climate, 2 °C and 3 °C warming worlds in India. The exceedance probability of the observed hottest summers shows a rise of more than seven and twenty-fold in the 2 °C and 3 °C warming world, respectively, compared to the present climate. The projected increases in the frequency of the hot summers and associated heatwave days will pose great societal challenges in the future in India.